Efisiensi Perbankan Daerah Di Indonesia - Chitra Laksmi Rithmaya; - Anggraeni (MediaTrend, 2021)
The development of banking industry in Indonesia could bring impact on the economic growth, especially in the face of the financial crisis. This study aims to examine scientifically the efficiency score of regional development banks. Furthermore, it also aims to understand further what factors influence the efficiency performance of regional development banks in Indonesia using the SFA (Stochastic Frontier Analysis) approach. The data used is from 25 Regional Development Banks (BPD) in Indonesia with the financial reporting period of 2011 to 2017. The results obtained are the level of efficiency of BPD in Indonesia does not reach 100%. The highest level of efficiency was at 97.80% in 2016. Then, the variable that affects bank efficiency is liquidity as measured by LDR, and credit risk as measured by NPL. Meanwhile, the variables of bank capital and profitability as well as the size of the bank and board of commissioners do not affect the efficiency of banks, especially Regional Development Banks in Indonesia in the period of 2011-2017.